Gaming Anthropology: The Problem of External Validity and the Challenge of Interpreting Experimental Games. Issue 4 (14th October 2020) - Naar, Nicole
ABSTRACT: Experimental economic games are an increasingly common component of the anthropological tool kit. Yet their external validity continues to be a point of debate and active empirical investigation within economics and anthropology. I review and reorganize central concepts within the experimental economic game literature on external validity and find that—consistent with anthropological assumptions of cultural variability—game results are not reliably generalizable across different participants or contexts. However, whether or not game behavior parallels real‐world behavior within the same participants or contexts remains an open question. Methodological diversity is a strength of anthropology as a discipline, and therefore anthropologists are well poised to design more effective tests of parallelism in the future. In the meantime, anthropologists borrowing experimental methods from economics should treat the relationship between behavior inside and outside of games as an open empirical question. They should also carefully consider whether the method is consistent with their theoretical assumptions and research goals. [ experimental economic games, external validity, generalizability, parallelism, anthropological methods ] RESUMEN: Juegos económicos experimentales son un componente cada vez más común del equipo de herramientas antropológicas. Sin embargo, su validez externa continúa siendo un punto de debate e investigación empírica activa dentro de la economía y la antropología. Reviso y reorganizo conceptos centrales dentro de la literatura de juegos económicos experimentales sobre la validez externa y encuentro que –consistente con asunciones antropológicas de variabilidad cultural– los resultados de los juegos no son generalizables de forma confiable a través de diferentes participantes o contextos. Sin embargo, si el comportamiento del juego paralela o no el comportamiento del mundo real dentro de los mismos participantes o contextos permanece como una pregunta abierta. Diversidad metodológica es una fortaleza de la antropología como una disciplina, por lo tanto, antropólogos están bien posicionados para diseñar pruebas más efectivas de paralelismo en el futuro. Entre tanto, antropólogos prestando métodos experimentales de la economía podrían tratar la relación entre el comportamiento dentro y fuera de los juegos como una pregunta empírica abierta. Deberían también considerar cuidadosamente si el método es consistente con sus asunciones teóricas y metas de investigación. [ juegos económicos experimentales, validez externa, capacidad de ser generalizable, paralelismo, métodos antropológicos ]